Cold Thermal Irrigation Decreases the Ipsilateral Gain of the Vestibulo-Ocular Reflex. Issue 3 (May 2017) - Tamás, Laszlo T.; Weber, Konrad P.; Bockisch, Christopher J.; Straumann, Dominik; Lasker, David M.; Büki, Béla; Tarnutzer, Alexander A.
Abstract : Objectives: During head rotations, neuronal firing rates increase in ipsilateral and decrease in contralateral vestibular afferents. At low accelerations, this "push-pull mechanism" is linear. At high accelerations, however, the change of firing rates is nonlinear in that the ipsilateral increase of firing rate is larger than the contralateral decrease. This mechanism of stronger ipsilateral excitation than contralateral inhibition during high-acceleration head rotation, known as Ewald's second law, is implemented within the nonlinear pathways. The authors asked whether caloric stimulation could provide an acceleration signal high enough to influence the contribution of the nonlinear pathway to the rotational vestibulo-ocular reflex gain (rVOR gain) during head impulses. Design: Caloric warm (44°C) and cold (24, 27, and 30°C) water irrigations of the left ear were performed in 7 healthy human subjects with the lateral semicircular canals oriented approximately earth-vertical (head inclined 30° from supine) and earth-horizontal (head inclined 30° from upright). Results: With the lateral semicircular canal oriented earth-vertical, the strongest cold caloric stimulus (24°C) significantly decreased the rVOR gain during ipsilateral head impulses, while all other irrigations, irrespective of head position, had no significant effect on rVOR gains during head impulses to either side. Conclusions: Strong caloric irrigation, which can only be achieved with cold water, reduces the rVOR gain during ipsilateral head impulses and thus demonstrates Ewald's second law in healthy subjects. This unilateral gain reduction suggests that cold-water caloric irritation shifts the set point of the nonlinear relation between head acceleration and the vestibular firing rate toward a less acceleration-sensitive zone.